In the eye of the beholder: investigating authority legitimization from distinct theoretical perspectives - Bożena Iwanowska; Julita Majczyk; Yan Kapranov (Journal of Modern Science)
Objectives This research critically examines legitimization in illiberal democracies, emphasizing its influence on governance.